Bauran Pemasaran Tirta Taman Mumbul Sebagai Wisata Spiritual Di Desa Sangeh, Kabupaten Badung - Anak Agung Intenia Amanda; Made Sukana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
This research purpose to analyze the marketing strategy in a spiritual tourism destination at Taman Mumbul, Sangeh, Badung regency. The qualitative research method are used in this research. The data composed are retrieved from observation, interviews, literature reviews, and literature study. Analysis steps of the data taken in this research are data collections, reductions, preparations, and drawing conclusion. This research find that based from the 4A as identification component of attraction, accessibility, amenity, and ancillary and The 7P as marketing mix application which include product, price, place, promotion, process, people, and physical evidence at Tirta Taman Mumbul, Sangeh Village, Abiansemal District, Badung Regency has goes well. Keyword: Spiritual Tourism, Marketing Mix, Tourism, Tirta Taman Mumbul